2020
DOI: 10.1101/2020.10.11.335232
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Light transport modeling in highly complex tissues using implicit mesh-based Monte Carlo algorithm

Abstract: The mesh-based Monte Carlo (MMC) technique has grown tremendously since its initial publication nearly a decade ago. It is now recognized as one of the most accurate Monte Carlo (MC) methods, providing accurate reference solutions for the development of novel biophotonics techniques. In this work, we aim to further advance MMC to address a major challenge in biophotonics modeling, i.e. light transport within highly complex tissues, such as dense microvascular networks, porous media and multi-scale tissue struc… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…In the first example, we use the rough-surface creation feature in Blender and investigate how changing the roughness of a skin-mimicking surface could lead to different light distributions and results. In the second example, we can combine BlenderPhotonics with one of our most recent advances in MC simulation – the implicit MMC (iMMC) algorithm 27 – to potentially enable the study of the impact of human hairs in fNIRS measurements. To the best of our knowledge, these types of studies have not been reported by other MC simulators.…”
Section: Blenderphotonics Application Showcasesmentioning
confidence: 99%
See 2 more Smart Citations
“…In the first example, we use the rough-surface creation feature in Blender and investigate how changing the roughness of a skin-mimicking surface could lead to different light distributions and results. In the second example, we can combine BlenderPhotonics with one of our most recent advances in MC simulation – the implicit MMC (iMMC) algorithm 27 – to potentially enable the study of the impact of human hairs in fNIRS measurements. To the best of our knowledge, these types of studies have not been reported by other MC simulators.…”
Section: Blenderphotonics Application Showcasesmentioning
confidence: 99%
“…A special script is used to export all hair vertices and the head mesh into a file that is processed by the Iso2Mesh toolbox to create iMMC simulation models for subsequent light transport simulations. 27…”
Section: Advanced Modeling Example 2 -Simulating Realistic Human Hair...mentioning
confidence: 99%
See 1 more Smart Citation
“…The lack of these accurate reflections meant a massive decrease in the accuracy of the simulation of the light distribution in the bottle, as the bottle acts as a cylindrical lens on the light, see SI 8. The vessels are a 3D synthetic microvascular network from data published in [45] and preprocessed by Yuan et al [46]. We model the slab of tissue using a box SDF (second shape in bottom left panel of Figure 1), and the vessels as a collection of capsule SDFs (third shape in top left panel of Figure 1) which are then joined together using the CSG operator union (bottom left operation in top right panel of Figure 1).…”
Section: Complex Geometrymentioning
confidence: 99%
“…8 More recently, hybrid approaches that combine shape representations offer further computational efficiency and accuracy. [12][13][14][15] These hybrid approaches include 1) dual-grid MMC (DMMC) 12 that combines a coarse tetrahedral mesh with a dense voxelated output volume, 2) splitvoxel MC (SVMC) 14 that combines curved surface meshes within a compact voxel data structure, and 3) implicit MMC (iMMC) 15 that combines a skeletal tetrahedral mesh with implicitly defined shapes such as tubes, spheres and thin membranes. These enhancements in modeling geometry have resulted in significantly improved accuracy, which can be directly translated to further speed enhancement while achieving the same output accuracy as conventional approaches.…”
Section: Introductionmentioning
confidence: 99%